Cover Picture: Dissolution of Platinum in the Operational Range of Fuel Cells (ChemElectroChem 10/2015). Issue 10 (23rd September 2015) - Cherevko, Serhiy; Keeley, Gareth P.; Geiger, Simon; Zeradjanin, Aleksandar R.; Hodnik, Nejc; Kulyk, Nadiia; Mayrhofer, Karl J. J.
<x xml:space="preserve">Abstract</x> The Front Cover picture depicts the dissolution of carbon‐supported platinum fuel cell catalyst in an acidic electrochemical environment. Detection of dissolved species is made possible by employing a unique combination of a novel scanning flow cell and an inductively coupled plasma mass spectrometer. The implications of the studied platinum dissolution processes for fuel cell catalyst stability are discussed. More details can be found in the Article by S. Cherevko, Karl J. J. Mayrhofer et al. on page 1471 in Issue 10, 2015 (DOI: 10.1002/celc.201500098).